Mastering machine learning with Python in six steps : a practical implementation guide to predictive data analytics using Python - Swamynathan, Manohar (Apress, 2019)
Your practical guide to moving from novice to master in machine learning with Python 3 in six steps, this book covers fundamental to advanced topics gradually helping beginners become worthy practitioners. --